Optimizing Patient Selection for Irreversible Electroporation of Locally Advanced Pancreatic Cancer: Analyses of Survival - Woeste, Matthew R.; Wilson, Khaleel D.; Kruse, Edward J.; Weiss, Matthew J.; Christein, John D.; White, Rebekah R.; Martin, Robert C. G. (Frontiers in Oncology, 2022)
Background:Irreversible electroporation(IRE) has emerged as a viable consolidative therapy after induction chemotherapy, in which this combination has improved overall survival of locally advanced pancreatic cancer(LAPC). Optimal timing and patient selection for irreversible electroporation remains a clinically unmet need. The aim of this study was to investigate preoperative factors that may assist in predicting progression-free and overall survival following IRE. Methods:A multi-institutional, prospectively maintained database was reviewed for patients with LAPC treated with induction chemotherapy followed by open-technique irreversible electroporation from 7/2015-5/2019. RECIST 1.1 criteria were used to assess tumor response and radiological progression. Overall survival(OS) and progression-free survival(PFS) were recorded. Survival analyses were performed using Kaplan Meier and Cox multivariable regression analyses. Results: 187 LAPC patients(median age 62 years range, 21 – 91, 65% men, 35% women) were treated with IRE. Median PFS was 21.7 months and median OS from diagnosis was 25.5 months. On multivariable analysis, age